National identity and national interests of Kazakhstan in the context of globalization - Sheryazdanova Г.Р.; Abildina Х.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The article discusses issues of national identity and the uniqueness of the cultural code of the Kazakh people in the context of globalization. The article highlights several subject areas of research, including issues of national and ethno-cultural identity of Kazakhstan society, cultural and historical features of its formation in the era of globalization. These issues take into account the specifics of Kazakhstan society in terms of world politics and history. In asking questions about the place of the Kazakh people on the world stage, we consider several aspects: a description of the Kazakh people, their values, the principles on which they are guided, their main priorities and the ideas that inspire them, the importance of Kazakhstan’s national interests and the uniqueness of its cultural code in a globalized world.